Aspek Sosial Pada Novel Perjalanan Menuju Langit KaryaMuhammad Muhsin Lahajji: Tinjauan Sosiologi Sastra DanImplementasi Dalam Pembelajaran Sastra Di SMA - FIirman Indrawan, Rafiana; , Prof. Dr. Ali Imron Al-Ma'ruf, M.Hum (2016)
The purpose of this study is (1) To describe the background sosiohistoris Muhammad Muhsin Lahajji author of the novel Journey to the Sky, (2) Describe the structure that builds on the novel Journey to Heaven, (3) Reveal the social aspects contained in the novel Journey to the sky with a sociological approach literature, (4) and describe the implementation of the novel in high school learning. This study used descriptive qualitative research object social aspects contained in the novel Journey to Heaven. This research data is a word, phrase, sentence and discourse in the novel Journey to Heaven. The data source is divided into two, namely primary and secondary data sources. Sources of primary data in this study is novel Journey to Heaven and secondary data sources is the author biographies novel Journey to Heaven. Data collection techniques in this study using the technique of literature, see, and record. Mechanical validity of the data using triangulation data. Data analysis technique used is the dialectic analysis techniques with the concept of "whole-part" and "understandingexplanation". The results of the analysis as follows: (1) the socio-historical background Lahajji Muhammad Muhsin, a novelist of the western Sumatra Sawahlunto. His name is known by his first novel Journey to the Sky that nomination in the race Republika novel 2012, (2) structure that were examined in the study novel Journey to the Sky consists of a theme and the fact the story. Themes novel Journey to the Sky is the human behavior in the search for the meaning of true love to find the woman of his dreams. The main character is a major Alfi, while the minor characters is Tila and Ainun, some additional figures such as Vice figures, figures extras. Grooves contained in this novel is the groove forward. Background place in the novel Journey to the Sky occurred in Talawi Sawahlunto West Sumatra city of Padang. Timescapes namely Alfi childhood to adulthood, and social background that mining atmosphere in society Padang. (3) The social aspect contained in the novel Journey to the Sky terms of the sociology of literature is divided into four factors: culture, religion, environment, and economy. The cultural aspects related to customs, and education. Aspects related to the value of religious worship and monotheism. Environmental aspects related to social class and profession. Economic aspects related to income, poverty, lifestyle. (4) The results of this study can be implemented on learning in high school literature class XI 1st half with SK 7. Understand the novel saga Indonesia / novels in translation, and KD 7.2 Analysing the elements of intrinsic and extrinsic novel Indonesia / translation.